2020
DOI: 10.4110/in.2020.20.e41
|View full text |Cite
|
Sign up to set email alerts
|

The Progression of SARS Coronavirus 2 (SARS-CoV2): Mutation in the Receptor Binding Domain of Spike Gene

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is a positive-sense singlestranded RNA (+ssRNA) that causes coronavirus disease 2019 . The viral genome encodes twelve genes for viral replication and infection. The third open reading frame is the spike (S) gene that encodes for the spike glycoprotein interacting with specific cell surface receptor -angiotensin converting enzyme 2 (ACE2) -on the host cell membrane. Most recent studies identified a single point mutation in S gene. A single point mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 19 publications
3
33
0
Order By: Relevance
“…E484K mutation on the spike protein causes SARS-CoV 2 escape from the neutralizing effect of the human immune systems mediated by antibody (Mahase 2021). On the other hand, D614G mutation on the spike protein has high infectivity in human cells having ACE2 receptors (Ogawa et al 2020, Kim et al 2020). D614G mutation situated exactly at the receptor binding domain of the spike protein.…”
Section: Resultsmentioning
confidence: 99%
“…E484K mutation on the spike protein causes SARS-CoV 2 escape from the neutralizing effect of the human immune systems mediated by antibody (Mahase 2021). On the other hand, D614G mutation on the spike protein has high infectivity in human cells having ACE2 receptors (Ogawa et al 2020, Kim et al 2020). D614G mutation situated exactly at the receptor binding domain of the spike protein.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study found four mutation sites in Korean COVID-19 patients ( 75 76 ). The physiographic map demonstrated three new mutation sites, G504D, V524D, P759L are indicated by blue letters, as well as the aforenamed D614G is characterized by red letters in Fig.…”
Section: Mutation Of S Glycoprotein In Infectivity and Immunogenicitymentioning
confidence: 96%
“…These mutations may prove that SARS-CoV was originated from an animal reservoir and adapted to human hosts. Overall, 22 different point mutation sites in RBD showed including additional 14 mutaion sites in other domains in Table 1 ( 74 ), but those mutations are not overlapped with three new mutations in Korean COVID-19 patients ( 75 76 ). A report from the US showed 14 mutations in the S glycoprotein of SARS-CoV-2.…”
Section: Mutation Of S Glycoprotein In Infectivity and Immunogenicitymentioning
confidence: 98%
See 2 more Smart Citations